(untitled) (Religious dialogue and cooperation, 2023)
The concept of national security belongs to the so-called old, traditional approaches to security. Its focus is on the survival of the sovereign state, which is its territorial integrity and political independence (sovereignty) protected by diplomatic, intelligence and military capacities, which is ability to repel military aggression or respond successfully. It is therefore justifiably called the concept of state security. In the real socialist countries, state security meant the state of protection of the state from political crime, as well as the security of the (socialist, communist) regime. Therefore, national or state security was in principle divided into so-called external (security from armed aggression) and internal (security of the regime and the state from the internal enemy). The primary bearers of the fight against all occurrences of security threats, as well as the functioning of the security function of the state, are the institutions, organizations and security services. The intelligence and security services as an integral part of the security and intelligence system work to detect, prevent and suppress any occurrence of security threats to a particular country or social union. Through the establishment and organization of a security system or security-intelligence system, the state strives to achieve its vital interests, to preserve its sovereignty, territorial integrity, constitutional order and the freedoms and rights of its citizens, in order to achieve the strategic goals of the state - membership in NATO and the European Union, which will bring even greater regional and continental security and stability. The focus of the modern concept of national security is the security of the state, society and the individual. Our country must strive for internal reforms, in terms of restoring the criteria of the rule of law, freedom of the media, control over the executive branch, which have long been considered unfulfilled.